Abitare e interpretare l'esistente : Case Nuove, Rosarno - Multari, Giovanni; Cortesi, Isotta (TeA / Teaching Architecture, 2022)
The publication collects results of the teaching experience carried out during the first semester of the academic year2020/21 within four design studios in Architectural Design and Landscape Architecture 3 of the Degree Course inArchitecture 5UE, at the Department of Architecture of the University of Naples "Federico II". The common theme is"LIVING AND INTERPRETING THE EXISTING", and the case study is the Case Nuove district in the municipality ofRosarno, province of Reggio Calabria.Dwelling interprets, starting from the investigations on the city and the landscape, the values ​​of the relationshipsbetween the different transformation processes, in order to strengthen the juxtaposition between Architecture andLandscape and, in this sense, each laboratory has identified strategies pertinent to regenerating the consolidatedspace we live in.The definition of a Common and Collective Living becomes an investigation tool that moves between public andprivate living in an experimental way, with the aim of investigating a dimension of the project open to change andinteraction between knowledge, capable of defining those new responses that are necessary and adequate today tothe critical issues of living in the present times.